PERSIAN COMMUNITY OF VLADIKAVKAZ IN THE CONTEXT OF SOCIOPOLITICAL CHANGES (1917-1930) - Kanukova, Zalina Vladimirovna; Tuaeva, Berta Vladimirovna; Plieva, Zalina Timurovna; Kalirad, Ali (History, Archeology and Ethnography of the Caucasus, 2023)
This article examines the Persian community of Vladikavkaz during the early 20th-century revolutions, the Civil War and its aftermath, repeated shifts in political regimes, and the establishment of Soviet rule. The significance of this study lies in the current magnitude of migration flows, the diaspora’s role as a key actor in international relations, and the limited knowledge available on the Persian community of the North Caucasus during the Soviet era, along with the historiographical situation. Notably, Iranian historians have previously believed that Persians who suffered from pogroms emigrated to their homeland in 1919; the pre-revolutionary Russian sources, with their varied terminology for Persians (Persians, Shiites, Tatars, etc.), have contributed to confusion regarding the ethnicity of migrants. This article introduces previously uncirculated sources that unequivocally demonstrate the presence of a Persian community in Vladikavkaz during the period under investigation, rather than simply an Azerbaijani community. This research employs a historical-systemic methodology, examining all events, plots, and narrative materials as a single process of adaptation by Persian migrants to a new political regime. The analysis of periodicals and official documentation, including meeting minutes and reports from various national structures, reveals practices of “indigenization” towards the Persians. The study uncovers the consequences of transitioning from traditional diaspora institutions to new forms of support for national minorities, and the role these plays in engaging Persians in Soviet society. The findings indicate that the liquidation of the Persian community was the result of several interconnected factors: the curtailment of the New Economic Policy (NEP), the abandonment of the “indigenization” policy, an anti-religious campaign, and a shift in the USSR’s foreign policy towards Iran. These developments collectively undermined the foundations of ethnic entrepreneurship, fostered ethnocultural discomfort, deprived the Persians of their main consolidating center – the consulate – and ultimately led to the deportation of the remaining Persians in the region to their homeland.
Keywords: Vladikavkaz; revolution; civil war; socio-political transformations; Persians; adaptation; deportation